Effects of Coke Deposits on the Catalytic Performance of Large Zeolite H‐ZSM‐5 Crystals during Alcohol‐to‐Hydrocarbon Reactions as Investigated by a Combination of Optical Spectroscopy and Microscopy. Issue 48 (14th October 2015) - Nordvang, Emily C.; Borodina, Elena; Ruiz‐Martínez, Javier; Fehrmann, Rasmus; Weckhuysen, Bert M.
Abstract: The catalytic activity of large zeolite H‐ZSM‐5 crystals in methanol (MTO) and ethanol‐to‐olefins (ETO) conversions was investigated and, using operando UV/Vis measurements, the catalytic activity and deactivation was correlated with the formation of coke. These findings were related to in situ single crystal UV/Vis and confocal fluorescence micro‐spectroscopy, allowing the observation of the spatiotemporal formation of intermediates and coke species during the MTO and ETO conversions. It was observed that rapid deactivation at elevated temperatures was due to the fast formation of aromatics at the periphery of the H‐ZSM‐5 crystals, which are transformed into more poly‐aromatic coke species at the external surface, preventing the diffusion of reactants and products into and out of the H‐ZSM‐5 crystal. Furthermore, we were able to correlate the operando UV/Vis spectroscopy results observed during catalytic testing with the single crystal in situ results. Abstract : It's the real thing : The catalytic activity of large zeolite H‐ZSM‐5 crystals in alcohol‐to‐olefin conversions was investigated and, using operando UV/Vis measurements, the catalytic activity and deactivation was correlated with the formation of coke. Furthermore, these findings were related to in situ single crystal UV/Vis and confocal fluorescence micro‐spectroscopy allowing the observation of the spatiotemporal formation of intermediates and coke species (see figure).